Intensification of “river in the sea” along the western Bay of Bengal Coast during two consecutive La Niña events of 2020 and 2021 based on SMAP satellite observations - Li, Zhiyuan; Long, Yu; Zhu, Xiao-Hua; Papa, Fabrice (Frontiers in Marine Science, 2023)
A narrow strip of low salinity water that hugs the western Bay of Bengal (BoB) is known as a “river in the sea” (RIS). During the autumns of 2020 and 2021, Soil Moisture Active Passive (SMAP) identified an intensification of the RIS that was characterized by a continuous, uniform strip of low salinity water (<31 psu) that was 100 km wide extending along the western BoB coast to south of Sri Lanka. The analysis shows that the La Niña events in 2020–2021 were responsible for this intensification. During the La Niña events of 2020 and 2021, cyclonic circulation anomalies were generated along the BoB coast, causing a stronger Eastern Indian Coastal Current (EICC). Meanwhile, the northern BoB received increased river discharge during the summer monsoons of the two years. The stronger EICC and increased river discharge together led to anomalous freshwater transport that contributed to the intensification of the RIS. Notably, the RIS extended far southward during La Niña events of 2016 and 2017. However, the spatial structure of the RIS differed sharply between 2016–2017 and 2020–2021. The results indicate that pairs of eddies in the western BoB steered the freshwater offshore by several hundred kilometers. As a result, offshore extending tongue-shaped freshwater plumes were formed that inhibited the formation of an organized RIS structure along the western BoB coast during 2016–2017. This study highlights that the year-to-year variability of the RIS was significantly influenced by the La Niña events and modulated by mesoscale processes.